AN ANALYSIS ON POLITENESS IN SMS OF THE STUDENTS TO THE LECTURERS OF ENGLISH DEPARTMENT UNIROW TUBAN - admin admin; Agus Wardhono (Universitas Muhammadiyah Gresik, 2013)
The purposes of this study are to find out politeness strategies and the dominant politeness strategies in Short Message Service (SMS) text of the students of English period 2008 sent to the lecturers of English from March to May 2012. This study applies qualitative research. Using documentation method, the data are collected from the lecturers' mobile phone by making permission from the lecturers to send the students' SMS that they received to the writer' mobile phone. The data are analyzed using Brown and Levinson's politeness theory (1987). The results reveal that there are four politeness strategies in students' SMS- Bald on Record (BOR), Positive Politeness (PP), Negative Politeness (NP), and Off Record (OR). Negative politeness strategy is dominantly used by the students. But the students' SMS cannot reflect appropriateness in their interpersonal communication to lecturers since the SMS of the students of English period 2008 sent to the lecturers are not consistent with Brown and Levinson's politeness theory, that lower status members tend to be relatively indirect (polite) in their communication to higher-status superior.